Study on Quality of Soil: Part-II. Simultaneous Determination of Cu, Pb, Cd, and Zn in Soil Samples of Bhusawal Area by Square Wave Voltammetry, Differential Pulse Polarographic and Differential Pulse-anodic Stripping Voltammetry: Study on Quality of Soil: Part-II. Simultaneous Determination of Cu, Pb, Cd, and Zn in Soil Samples of Bhusawal Area by Square Wave Voltammetry, Differential Pulse Polarographic and Differential Pulse-anodic Stripping Voltammetry - Patil, Manisha (International Journal of Pharmaceutical & Biological Archive, 2018)
The analytical procedure has been developed for simultaneous determination of the toxic trace metals Cu, Pb, Cd, and Znin soil samples from Bhusawal, employing electrochemical techniques, namely square wave voltammetry, differential pulse polarographic, and anodic stripping voltammetry (DP-ASV) techniques at hanging mercury drop electrode. The soil samples were collected from Bhusawal area, at five points, in March 2016. The metals were made free from any interference, and the applicability of the method has been proved by the analysis of soil samples from polluted and non-polluted area. Accuracy is verified by employing atomic absorption spectrometry. Simultaneous determination by the polarographic and voltammetric method for studied four metals and calculation of concentration level of each metal in the collected samples from the selected area was studied. The results and conclusions were discussed.